A PERAN PENDIDIKAN KARAKTER DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA PADA KELAS B DI KB BAITAL HAMDI SAMPANG: PERAN PENDIDIKAN KARAKTER DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA PADA KELAS B DI KB BAITAL HAMDI SAMPANG - Khorofi, Moh (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2025)
This research aims to analyze the contribution of character education in increasing the self-confidence of class B students at KB Baital Hamdi Sampang. This research uses a descriptive qualitative approach with data collection methods in the form of observation, interviews and documentation. Data were analyzed through a process of reduction, presentation and drawing conclusions. The research results show that character education has an important role in building children's self-confidence. Its implementation is carried out through several habits, namely: first, reading the iqra every morning to form noble morals; second, telling stories about the diversity of characters to encourage children to ask and answer; third, using games that can increase self-confidence; fourth, give children the opportunity to try new things; and fifth, teachers recognize children's personalities and characters so that character formation is more effective. This research emphasizes the importance of character education in forming self-confidence in children.